DESKRIPSI KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATERI FUNGSI KUADRAT DI KELAS X SMA - Paramida, Resmita; Hamdani, Hamdani; T, Ahmad Yani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractMathematics is a subject that contains a lot of abstract ideas and concepts and bases itself on agreements and uses a deductive mindset consistently. Mathematics is a science that has basic abstract objects in the form of facts, concepts, operations, and principle. This research aimed to describe what kinds of errors students make on quadratic function material of SMA Mujahidin Pontianak. The research method used in this study is descriptive. The techniques used were measurement techniques and direct communication techniques with data collection tools student?s errors test and interview guide. The subject of this research was students of SMA Negeri Mujahidin Pontianak. Based on the results of research and description it can be concluded that the types of errors students make in solving quadratic functions are: comprehension errors, process skill errors, and careless errors. These errors occur because of weak understanding of concepts, lack of mastery of principles, and lack of attention in performing calculations. Keywords: Description, Student Errors, Quadratic Functions